Response surface optimization of fluidized roasting reduction of low-grade pyrolusite coupling with pretreatment of stone coal - Feng, Yali; Cai, Zhenlei; Li, Haoran; Du, Zhuwei; Liu, Xinwei (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
Research on the novel technology of fluidized roasting reduction of low-grade pyrolusite coupling with pretreatment of stone coal has been conducted. According to the response surface design and the analysis of results, orthogonal experiments have been conducted on the major factors and effects of the factors on the manganese reduction efficiency have been studied. The quadratic model between the manganese reduction efficiency and the factors has been established. Meanwhile, the contour or 3D response surface of the manganese reduction efficiency among various factors has been presented. The maximum manganese reduction efficiency could be optimized to nearly 100 %, when the mass ratio of stone coal to pyrolusite was 2.5:1, the roasting temperature of stone coal was 1080 ℃, the roasting temperature of pyrolusite was 775 ℃, and the roasting time was 2 h. The results of the manganese reduction efficiency of the actual experiments were close to those of the fitting model by the verification experiments, indicating that the optimum solution has a relatively high reliability. Other low-grade pyrolusite such as Guangxi pyrolusite (China), Hunan pyrolusite (China), and Guizhou pyrolusite (China) were tested and all these materials responded well giving nearly 100 % manganese reduction efficiency.